2000
DOI: 10.1523/jneurosci.20-09-03244.2000
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Bias and Lineage Restriction in the Phenotype Determination of Dopamine and Neuropeptide Y Amacrine Cells

Abstract: Blastomere lineages are differentially biased to produce different neurotransmitter subtypes of amacrine cells (Huang and Moody, 1995, 1997,). To elucidate when this bias is acquired, we examined amacrine lineages at different early developmental times. Our experiments demonstrate that the bias to express dopamine and neuropeptide Y amacrine fates involves several steps before the formation of the definitive optic cup. At cleavage stages, a retinal progenitor that contributes large numbers of cells is already … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Barhl2, probably together with Pax6, then promotes the differentiation of glycinergic amacrine cells from faterestricted amacrine progenitors. Such fate-restricted amacrine progenitors have been identified by fate tracing experiments in early rat and Xenopus retinas (Alexiades and Cepko, 1997;Huang and Moody, 1997;Moody et al, 2000). However, it remains to be determined what factors are involved in the differentiation of GABAergic amacrine cells.…”
Section: Barhl2 Promotes the Differentiation Of Glycinergic Amacrine mentioning
confidence: 99%
“…Barhl2, probably together with Pax6, then promotes the differentiation of glycinergic amacrine cells from faterestricted amacrine progenitors. Such fate-restricted amacrine progenitors have been identified by fate tracing experiments in early rat and Xenopus retinas (Alexiades and Cepko, 1997;Huang and Moody, 1997;Moody et al, 2000). However, it remains to be determined what factors are involved in the differentiation of GABAergic amacrine cells.…”
Section: Barhl2 Promotes the Differentiation Of Glycinergic Amacrine mentioning
confidence: 99%
“…Several other members of the GABA and glutamate transporter families have been reported in mammals, and it remains a possibility that subpopulations within these neurotransmitter phenotypes are biased by early lineage. If different subtypes were produced by different subsets of progenitors, an analysis of the entire class, such as that performed in the current study, would be unable to reveal fate bias (Moody et al, 2000).…”
Section: Lineage Biasmentioning
confidence: 84%
“…1A). Lineage tracing experiments in Xenopus have shown that both the early retinogenic blastomeres and the cells of the eye field are not homogeneous populations, being composed of cells with different potentialities (Moody et al, 2000). For instance, individual retinogenic blastomeres are differentially biased to generate distinct subsets of amacrine cells.…”
Section: Initial Specification Of Retinal Cell Fatementioning
confidence: 99%
“…For instance, individual retinogenic blastomeres are differentially biased to generate distinct subsets of amacrine cells. Similarly, eye field cells can be grouped into two classes: multipotent progenitors that will generate all the retinal cell types and progenitors with a more restricted potential, giving rise to cells of a single retinal layer (Moody et al, 2000). It is unclear whether the mixed cell population of the eye field may reflect the co‐existence of progenitors in two determinative states, displaying progressively restricted potentialities, or, rather, distinct primary and secondary progenitors that will give rise to the larval and the adult retina, respectively.…”
Section: Initial Specification Of Retinal Cell Fatementioning
confidence: 99%